Evolving doublesex expression correlates with the origin and diversification of male sexual ornaments in the Drosophila immigrans species group. Issue 2 (25th January 2018) - Rice, Gavin; Barmina, Olga; Hu, Kevin; Kopp, Artyom
Abstract : Male ornaments and other sex‐specific traits present some of the most dramatic examples of evolutionary innovations. Comparative studies of similar but independently evolved traits are particularly important for identifying repeated patterns in the evolution of these traits. Male‐specific modifications of the front legs have evolved repeatedly in Drosophilidae and other Diptera. The best understood of these novel structures is the sex comb of Drosophila melanogaster and its close relatives. Here, we examine the evolution of another male foreleg modification, the sex brush, found in the distantly related Drosophila immigrans species group. Similar to the sex comb, we find that the origin of the sex brush correlates with novel, spatially restricted expression of the doublesex ( dsx ) transcription factor, the primary effector of the Drosophila sex determination pathway. The diversity of Dsx expression patterns in the immigrans species group closely reflects the differences in the presence, position, and size of the sex brush. Together with previous work on sex comb evolution, these observations suggest that tissue‐specific activation of dsx expression may be a common mechanism responsible for the evolution of sexual dimorphism and particularly for the origin of novel male‐specific ornaments.